The Effect Of The Strategy Of Clarifying Values On The Expressive Performance Of Fifth-Grade Literary Students (Journal of the College of Basic Education, 2024)
The current research aims to find out (the effect of the value clarification strategy on expressive performance(33,To achieve the goal of the research, the researcher followed the experimental approach with the aim of reconciling the research procedures and how to reach the results. The researcher followed an experimental design with partial control for two equal independent groups (experimental and control)The same (successive post-tests of expressive performance), and the researcher selected a random sample of (66) female students from the fifth literary grade in the middle school.Sanabel Al-Khair is affiliated with the Baghdad Education Directorate The third Karkh, with (33) students for the experimental group, and (33) students for the control group. The researcher taught the experimental group students using the values clarification strategy, studied the same topics in the usual way, and rewarded them. The researcher tested the students of both groups on a number of variables: chronological age, academic achievement, previous years’ grades, and intelligence test. Al-Baha presented the expressive topics to a group of experts and arbitrators, and prepared teaching plans for the two groups and presented them to the arbitrators to benefit from their opinions and experiences. The researcher chose the first semester to teach the two research groups, where the researcher studied the two groups for a period of (8) weeks, which is the duration of the experiment, as it began on Monday on(16|10|2023) and ended on Tuesday (26|12|2023), and the test was conducted.The two groups dealt with specific topics of critical performance, after the researcher taught them to the students for research purposes, and in order to apply them to the two research groups, the following statistical methods were used: (T-test for two, independent samples, Smirnov test, Levene test, Ca2 test, Eta square equation). The researcher found this,The following result: Fifth grade female students excelled in the literary subject in the experimental group The fifth grade literary students in the control group were taught expression using the (clarifying values) method, while those in the control group were taught expression using the regular method. In light of the research results, the researcher concluded the following: Al-Dass method (clarification Values) in expressive performance led to improving the level of expressive performance among female students in the class The fifth is clearly and concretely literary. In continuation of this research, the researcher proposed conducting a number of studies that aim to determine the effect of (clarifying values) on expressive performance in... Disturbing stages of study